Advances in Surface-Enhanced and Tip-Enhanced Raman Spectroscopy, Mapping and Methods Combined with Raman Spectroscopy for the Characterization of Perspective Carbon Nanomaterials - Marianna V. Kharlamova (Nanomaterials, 2023)
Surface-enhanced Raman spectroscopy (SERS) is based on the effect of the plasmonic enhancement of intensity of the Raman scattering of molecules in cases when they are adsorbed on a substrate [...]